Advances in Artificial Intelligence and Security: 8th International Conference on Artificial Intelligence and Security, ICAIS 2022, Qinghai, China, July 15-20, 2022, Proceedings, Part III - Sun, Xingming; Zhang, Xiaorui; Xia, Zhihua; Bertino, Elisa (Communications in Computer and Information Science, 2022)
The 3-volume set CCIS 1586, CCIS 1587 and CCIS 1588 constitutes the refereed proceedings of the 8th International Conference on Artificial Intelligence and Security, ICAIS 2022, which was held in Qinghai, China, in July 2022. The total of 115 full papers and 53 short papers presented in this 3-volume proceedings was carefully reviewed and selected from 1124 submissions. The papers were organized in topical sections as follows:Part I: artificial intelligence;Part II: artificial intelligence; big data; cloud computing and security; multimedia forensics;Part III: encryption and cybersecurity; information hiding; IoT security.